A Novel Natural Source Sterculia foetida Fruit Shell Waste as Colorant and Ultraviolet Protection for Linen. Issue 3 (4th May 2018) - Teli, M. D.; Pandit, Pintu
ABSTRACT: There has been a growing interest in natural dyes and consciousness about ill effects of ultraviolet rays on the human skin. This paper discusses dye extraction from the fruit shell waste of Sterculia foetida and its application on linen fabric for dyeing as well as ultraviolet protection (UPF) property. Optimal results were achieved for dyeing at 90°C for 60 min at 30% concentration of the dye on the weight of fabric using pre- and post-mordant dyeing techniques. Dyeing on linen fabric with and without mordant showed very good results in terms of different hues of color and UPF. Treated fabrics showed substantial increase in color depth and good to very good wash, light and rubbing fastness properties for both with and without mordant-dyed linen fabrics. The results confirmed that natural dye from Sterculia foetida fruit shell extract has potential applications for linen dyeing and producing a good to very good UPF.